Archives / V&A - Victoria and Albert Museum (2009)
[Dt.:] Die Victoria and Albert Museum Archives bestehen aus drei seperaten Archiven, dem Archive of Art and Design, der Beatrix Potter Collections und dem V&A Archive. Die Website bietet umfangreiche Informationen zu den Beständen. - [Engl.:] The Victoria and Albert Museum Archives are split into three separate archives: The Archive of Art and Design, The Beatrix Potter Collections and the V&A Archive. The website provides detailed information on the collections.